Synthesis and evaluation of some novel Schiff's and Mannich bases of indole-2,3-diones as potential antibacterial, analgesic and antiinflammatory agents - Pandeya S.N.; Sriram D.; Alagarsamy V. (My University, 2025)
Schiff's bases of indole-2,3-diones (isatin) and 5-methyl indole-2,3- diones (methyl isatin) with anthranilic acid have been synthesized by a novel methodology. Mannich bases of these Schiff's bases were also synthesized. The compounds synthesized were evaluated for antibacterial, analgesic and antiinflammatory activities. Some of the compounds synthesized were found to possess analgesic and antiinflammatory activities more than the standard diclofenac sodium.